ABRI di Tengah Paradoks Sosial - Suryo Adi Pramono (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 1998)
Since the Indonesian Army successfully has increased nation-state economic and welfare level (hand in hand with technocrats and foreign capitals), it has to face a new challenge, that is